Sound Absorption Behavior Related to Reduce the Melamine-Urea-Formaldehyde (MUF) Adhesives for the Coffee Silver Skin Board Production - Visit Eakvanich; Putipong Lakachaiworakun; Wachara Kalasee; Panya Dangwilailux (My University, 2023)
The development of sound-absorbing panels which used coffee-silver-skin (CS) and melamine-urea-formaldehyde (MUF) as a composite board was studied. In this experiment, the objective was to examine the impact on the sound absorption coefficient (SAC) when incorporating wood husk into the composite board, specifically in the cases of CS (100%) and CS (90%) mixed with wood husk (10%), while simultaneously reducing the amount of MUF adhesive and adding corn starch (25%). It was observed that as the MUF content of the board decreased to 75%, the sound absorption coefficient average (SAA) were found to be 0.59 and 0.62 for the middle- and high-frequency ranges, respectively. For the frequency range higher than 3.15 kHz, the maximum SAC value of sample boards was 0.91 and the noise reduction coefficient (NRC) value was 0.47. While, the result showed the maximum SAC and the NRC value of sample boards were 0.93 and 0.48, respectively above the frequency range higher than 1.25 kHz for decreasing the MUF adhesive of board to 50%. Similarly, the addition of wood husk and corn starch mixed to CS could increase the SAA value of sample boards in the middle- and high-frequency range.
Keywords: Husk; Urea-formaldehyde; Noise reduction coefficient; Acoustic Wave Phenomena Research